2D Optimization of Thin Perovskite/Silicon Four-Terminal Tandem Solar Cells - Chapa, Manuel Manta (2018)
A model capable of describing the optoelectronic response of tandem photovoltaic cells is introduced, employing commercial software provided by Lumerical Solutions Inc. Specifically, a four-terminal thin perovskite/silicon architecture is studied, with special focus on the optical properties of the interlayer, and also on the ITO contact problematic – tackled by an alternative design, where all but one transparent contact are comprised of state-of-the-art transparent metallic structured grids. Furthermore, a look into how light-trapping formalisms are essential to the suc-cess of this architecture is taken. Thus, this research aims to demonstrate the means to overcome one of the main constraints in tandem cells performance, the transparent oxide’s parasitic absorption characteristics. Addi-tionally, the possibility of highly efficient, thin and flexible, solar cells is explored, being con-cluded that these can be achieved with the referred architecture after careful optimization of the design parameters. The developed optoelectronic model can predict the response of heterojunc-tion solar cells, and also of modelling perovskite solar cells – aspects which are not commonly reported in recent literature. The parasitic absorption is reduced by 30% when replacing two ITO contacts by the novel metallic grid alternatives. Simultaneously, on a hypothetical light-management scenario where 10x optical path length in the bottom layer is implemented, up to 27% efficiency is achievable by the tandem device. The attained results can be used as a guideline for forthcoming architecture improvements showing promise for the future of thin and flexible photovoltaic applications.